Condition- and context-dependent alternative reproductive tactic in Drosophila prolongata. (17th November 2021) - Perdigón Ferreira, Jhoniel; Lüpold, Stefan
Abstract: Species with intense male–male competition for access to females often show alternative reproductive tactics (ARTs) where males of lower competitive ability adopt a sneaky behavior to gain access to mates. These ARTs are usually associated with intrasexual dimorphisms, in that males with distinct morphologies show different tactics. In some cases, however, males adopt different tactics without being dimorphic. Male Drosophila prolongata exhibit continuous variation in body size and shape, with enlarged forelegs that they use in male-male contests and in courtship, including stimulation of the female's abdomen. During this "leg vibration, " however, nearby males can intercept the courted female and mate without their own courtship. Here, we studied the causes and consequences of these different mating tactics in competitive mating trials between males varying in their size and shape. We found that male mating tactics were condition-dependent. Whereas large, high-condition males were more likely to show leg vibration in their courtship, smaller, lower-condition males were more likely to intercept. However, the number of offspring produced was independent of male condition and reproductive tactic. We discuss possible scenarios for the evolution and maintenance of the ARTs and some future directions for the study of ARTs in this species and in general. Abstract : When competing for access to mates, disadvantaged males can use parasitic mating tactics to reproduce. Drosophila prolongata males intercept courting rivals and steal females from them. This behavior is not linked to a specific morphology but represents an alternative tactic that depends on their condition and the context that males face. The study of alternative reproductive tactics can help to understand how variation within and between species is maintained.